Do commonalities facilitate private information channels? Evidence from common gender and insider trading - Scarlat, Elvira; Clacher, Iain; Garcia Osma, Beatriz; Shields, Karin (Elsevier, 2021)
We examine insider trading profitability and common identity between insiders and top executives. We argue that common gender and the resulting social connections influence access to private information, wherby insiders benefit from greater information-sharing with top executives of the same gender. Using a large sample of US firms between 1995 and 2016, we find higher (lower) insider trading profitability for female (male) insiders in the presence of a female CEO or CFO. We also find that, in isolation, other social and professional commonalities, such as age, ethnicity, having attended the same university or having worked at the same firm also increase insider profitability, albeit to a lesser extent. Our evidence suggests that some of these commonalities enhance the common gender effect when combined with it. We examine formal interactions and find that attending meetings and serving on committees with top executives of the same gender enables private information-sharing, consistent with gender acting as an informational channel. We also document greater clustering of insiders’ trades around the trades made by common gender top executives. Our findings are consistent with flows of private information from CEOs and CFOs to less informed common gender insiders.
Keywords: Gender; Information asymmetry; Insider trading; Social commonalities; Homophily; 53 Ciencias Económicas; ODS 5 - Igualdad de género; ODS 16 - Paz, justicia e instituciones sólidas